2023
DOI: 10.21203/rs.3.rs-2501566/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between Antibiotic Use and Subsequent Risk of Prostate Cancer: A Retrospective Cohort Study in South Korea

Abstract: Background Several studies suggest that antibiotic use may affect overall cancer incidence, but the association between antibiotics and prostate cancer is still unclear. Methods A population-based retrospective cohort study was conducted using the Korean National Health Insurance Service (NHIS) database. 1,032,397 individuals were followed up from January 1, 2007, to December 31, 2019. Multivariate Cox hazards regression was utilized to calculate adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently, Park et al. evaluated the association between antibiotic use and prostate cancer risk using a retrospective cohort of the Korean National Health Insurance Service database 5 . Overall, 1 032 397 individuals were included in the study population between January 1, 2007, and December 31, 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Park et al. evaluated the association between antibiotic use and prostate cancer risk using a retrospective cohort of the Korean National Health Insurance Service database 5 . Overall, 1 032 397 individuals were included in the study population between January 1, 2007, and December 31, 2019.…”
mentioning
confidence: 99%
“…The authors showed that using antibiotics for 180 or more days was associated with an increased risk of prostate cancer [adjusted hazard ratios (aHRs), 1.46; 95% confidence intervals (CI), 1.11–1.91]. Additionally, individuals who used four or more antibiotic classes had a higher risk of prostate cancer (aHR, 1.18; 95% CI, 1.07–1.30) than those who did not use antibiotics 5 . This study has some limitations.…”
mentioning
confidence: 99%
“…In this issue of the International Journal of Urology , Park and Hong et al. assessed the association between the use of antibiotics and their associated risk of prostate cancer by drawing on the Korean National Health Insurance Service (NHIS) database, which accounted for over 1 000 000 patients and concluded that long‐term use of antibiotics may affect the incidence of prostate cancer 4 . This is the first retrospective study evaluating the association between antibiotic use and prostate cancer in Asia and sheds new light on the long‐term use of antibiotics and associated risk of developing prostate cancer in Asian populations.…”
mentioning
confidence: 99%